2014
DOI: 10.1007/s10439-014-1154-x
|View full text |Cite
|
Sign up to set email alerts
|

Head Injury Potential and the Effectiveness of Headgear in Women’s Lacrosse

Abstract: Over the past 10 years, lacrosse has grown increasingly popular, making it one of the fastest growing team sports in the country. Similar to other sporting activities, head injuries in lacrosse can and do occur, and the number of lacrosse-related head injuries has increased in recent years. In women's lacrosse, protective headgear is not required, but U.S. Lacrosse and the American Society for Testing and Materials are currently working to develop a headgear standard for the women's game. In the interim, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
4
12
0
Order By: Relevance
“…The scaled peak linear parameter was lower than that for reported human brain concussion tolerances generated by the instrumented helmet data (Guskiewicz et al, 2007;Rowson et al, 2012) and below the reported linear acceleration within the range of concussion (61-144 g) (Rodowicz et al, 2015;Clark and Hoshizaki, 2016;Clark et al, 2018) but was higher than the head accelerations in volunteer soccer heading (23.5 g) (Shewchenko et al, 2005). The scaled peak angular velocity and peak angular deceleration were much higher than the reported threshold levels in the range of 3,958-12,832 rad/s 2 that were developed from the analysis of sports collisions resulting in a human concussion (Pellman et al, 2003;Rowson et al, 2012;Rowson and Duma, 2013;Mcintosh et al, 2014;Rodowicz et al, 2015;Clark and Hoshizaki, 2016). Considering that linear kinematics predict biological outcomes better than they do angular kinematics (Namjoshi et al, 2017) and that clinical concussion may occur under many different situations, the biomechanics in our model seemed to be reasonable.…”
Section: Biomechanical Analysismentioning
confidence: 54%
“…The scaled peak linear parameter was lower than that for reported human brain concussion tolerances generated by the instrumented helmet data (Guskiewicz et al, 2007;Rowson et al, 2012) and below the reported linear acceleration within the range of concussion (61-144 g) (Rodowicz et al, 2015;Clark and Hoshizaki, 2016;Clark et al, 2018) but was higher than the head accelerations in volunteer soccer heading (23.5 g) (Shewchenko et al, 2005). The scaled peak angular velocity and peak angular deceleration were much higher than the reported threshold levels in the range of 3,958-12,832 rad/s 2 that were developed from the analysis of sports collisions resulting in a human concussion (Pellman et al, 2003;Rowson et al, 2012;Rowson and Duma, 2013;Mcintosh et al, 2014;Rodowicz et al, 2015;Clark and Hoshizaki, 2016). Considering that linear kinematics predict biological outcomes better than they do angular kinematics (Namjoshi et al, 2017) and that clinical concussion may occur under many different situations, the biomechanics in our model seemed to be reasonable.…”
Section: Biomechanical Analysismentioning
confidence: 54%
“…Peak linear and rotational acceleration have been shown to have a low correlation to injury (Kleiven, 2007;Zhang et al, 2004), and it has been suggested that the resulting acceleration loading curve created from an impact, rather than the peak resultant accelerations, is more representative of actual brain injury . As such, the findings of Rodowicz et al (2015) and which solely examine peak linear and rotational acceleration may not be representative of actual brain response. Finite element modelling allows for the interpretation of linear and rotational acceleration curves and how they influence the response of brain tissue to an impact.…”
Section: Introductionmentioning
confidence: 99%
“…Some experts contend that the use of helmets is unnecessary (Goldenberg and Hossler, 1995;Harmer, 1993), while others encourage the use of helmets (Diamond and Gale, 2001;Lincoln et al, 2007;Otago et al, 2007). Recently, studies have examined the potential for helmets to reduce linear and rotational acceleration of a headform for women's lacrosse head impacts Rodowicz et al, 2015). Rodowicz et al (2015) assessed both soft headgear and a men's lacrosse helmet under stick and ball impacts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations